Prognostic impact of tumour‐infiltrating lymphocytes and cancer‐associated fibroblasts in patients with pancreatic adenocarcinoma of the body and tail undergoing resection. Issue 6 (21st January 2020) - Delayre, T.; Guilbaud, T.; Resseguier, N.; Mamessier, E.; Rubis, M.; Moutardier, V.; Fara, R.; Berdah, S. V.; Garcia, S.; Birnbaum, D. J.
Abstract : Background: The prognosis of patients with pancreatic cancer remains poor and novel therapeutic targets are required urgently. Treatment resistance could be due to the tumour microenvironment, a desmoplastic stroma consisting of cancer‐associated fibroblasts and tumour‐infiltrating lymphocytes (TILs). The aim of the study was to evaluate the prognostic value of TILs and cancer‐associated fibroblasts (CAFs) in pancreatic cancer of the body and tail. Methods: Using tissue microarray from resected left‐sided pancreatic cancer specimens, the immunohistochemistry of TILs (cluster of differentiation (CD) 45, CD3, CD4, FoxP3 and CD8), CAFs (vimentin and α‐smooth muscle actin (αSMA)) and functional markers (PD‐L1 and Ki‐67) was examined, and the association with disease‐free (DFS) and overall (OS) survival investigated using a computer‐assisted quantitative analysis. Patients were classified into two groups, with low or high levels or ratios, using the 75th percentile value as the cut‐off. Results: Forty‐three patients were included in the study. Their median DFS and OS were 9 and 27 months respectively. A high CD4/CD3 lymphocyte ratio was associated with poorer DFS (8 months versus 11 months for a low ratio) (hazard ratio (HR) 2·23, 95 per cent c.i. 1·04 to 4·61; P  = 0·041) and OS (13 versus 27 months respectively) (HR 2·62, 1·11 to 5·88; P  = 0·028). A low αSMA/vimentin ratio together with a high CD4/CD3 ratio was correlated with poorer outcomes. No significant association was found between Ki‐67, PD‐L1 and survival. Conclusion: In patients with resected left‐sided pancreatic cancer, a tumour microenvironment characterized by a high CD4/CD3 lymphocyte ratio along with a low αSMA/vimentin ratio is correlated with poorer survival. Abstract : To evaluate the prognostic value of tumour‐infiltrating lymphocytes (TILs) and cancer‐associated fibroblasts (CAFs) in pancreatic ductal adenocarcinoma (PDAC), this study investigated the correlation between lymphocyte infiltration (CD45, CD3, CD4, FoxP3, CD8), CAF expression (vimentin, α‐smooth muscle actin (αSMA)) and overall (OS) and disease‐free (DFS) survival in patients with resected left‐sided PDAC. CD, cluster of differentiation; FoxP3, forkhead box P3; IL, interleukin. Identify patients with the worst prognosis Abstract : Antecedentes: El pronóstico del cáncer de páncreas sigue siendo malo y se requieren nuevas dianas terapéuticas de forma urgente. La resistencia al tratamiento podría ser atribuida al microambiente tumoral, un estroma desmoplásico compuesto por fibroblastos asociados al cáncer y linfocitos infiltrantes de tumor. El objetivo del estudio fue evaluar el valor pronóstico de los linfocitos infiltrantes de tumor y de los fibroblastos asociados al cáncer en el cáncer de cuerpo y cola de páncreas. Métodos: Utilizando microarray para el análisis de muestras de tejido obtenidas tras la resección de cáncer de páncreas del lado izquierdo, se realizó inmunohistoquímica de linfocitos infiltrantes de tumor (CD45, CD3, CD4, FoxP3 y CD8), fibroblastos asociados al cáncer (vimentina y actina del músculo liso alfa (αSMA)) y marcadores funcionales (PD‐L1 y Ki67), y se investigó la asociación con la supervivencia libre de enfermedad y la supervivencia global. Los resultados se obtuvieron tras un análisis cuantitativo asistido por ordenador. Los pacientes se clasificaron en dos grupos, de bajo y alto riesgo, utilizando el valor del percentil 75 como punto de corte. Resultados: Se incluyeron 43 pacientes en el estudio. En esta población, la mediana de supervivencia libre de enfermedad y de supervivencia global fueron 9 meses y 27 meses, respectivamente. Una alta proporción de linfocitos CD4/CD3 se asoció a peor supervivencia libre de enfermedad (8 meses versus 11 meses; cociente de riesgos instantáneos, hazard ratio, HR 2, 2; i.c. del 95% 1, 0‐4, 6; P = 0, 041) y supervivencia global (13 meses versus 27 meses; HR 2, 6; i.c. del 95% 1, 1‐5, 9; P = 0.028). Una baja proporción αSMA/vimentina junto con una alta proporción CD4/CD3 se correlacionó con peores resultados. No se encontró asociación significativa entre Ki67, PD‐L1 y la supervivencia. Conclusión: En pacientes con cáncer de páncreas izquierdo resecado, un microambiente tumoral caracterizado por una alta proporción de linfocitos CD4/CD3 junto con una baja proporción de αSMA/vimentina se correlaciona con una peor supervivencia.